Making South African tertiary education multilingual: the implementation, monitoring and evaluation of SANTED Multilingualism Projects 2007 "“ 2010 - Nosilela, Bulelwa (Rhodes University, Faculty of Humanities, School of Languages and Literatures, 2020)
This thesis focuses on multilingualism as it applies to education, particularly higher education in South Africa. The thesis suggests that language must be seen as critical in education (Obanya, 2004; Wolff, 2006). This thesis also suggests that there is a link between a person's general competence in an educational environment, and that person's language competence. In support of other scholars, this thesis also finds that learners from low social classes in society have a restricted linguistic code and therefore the learners from these social classes lack the ability to express themselves in an elaborative manner in a cognitive situation while learners from upper social class have an elaborate linguistic repertoire in the language of instruction, namely English. Even though general policy in South Africa and Africa as a whole recognises this relationship between language and education, this thesis finds that very little is being done to implement these well-meaning policies. The SANTED (South Africa-Norway-Tertiary-Education) programme, which forms the focus of this thesis, is seen as an exception. While there is an increase in the number of learners and students accessing centres of learning, especially those from historically-disadvantaged backgrounds (CHE Higher Education Monitor, 2008), there is at the same time rigorous debate in South Africa at the moment as to whether these learners and students benefit optimally from knowledge offered in centres of learning, and are therefore, not accomplishing success expected from them (Boughey, 2008). This thesis suggests that at the centre of this debate is the understanding that, while there are a variety of factors that might affect their success, for example social and economic status, schooling background in case of students in higher education, language plays a pivotal role. This thesis analyses the challenges and successes which faced the SANTED programme at a number of South African institutions where language issues were brought to the centre of the learning process. The thesis also assesses best practices in various African countries and makes recommendations regarding language-use in Higher Education, as part of a transformationprocess. The collaboration between the South African and Norwegian governments provided impetus to policy implementation. It also had other focus areas such as capacity building, access, success and retention and collaboration with Southern African Developing Countries (SADC). This thesis shows, through a critical analysis of SANTED, that it represented an important intervention regarding the promotion of multilingualism.
Keywords: South Africa-Norway Tertiary Education Development Programme; Language policy -- South Africa; Multilingual education -- South Africa; Language and education -- South Africa; Education, Higher -- Social aspects -- South Africa